Complete Blood Count (CBC) Parameters and ICU Mortality of COVID-19 Disease in Delta Variant and Omicron Variant in a Community-Based Hospital in New York City: A Retrospective Observational Cohort Study - Ruchi Yadav; Vivek Yadav; Sindhu Pokhriyal; Umar Zahid; Anjula Gandhi (Medicine and Medical Research: New Perspectives Vol. 4, 2024)
Background: Severe Acute Respiratory Syndrome-Coronavirus-2 (SARS-CoV-2) is the official name of COVID-19, a respiratory infection that had the first case reported from the Hubei province of China on December 8, 2019. This virus is the main etiological agent behind the most dreaded pandemic of pneumonia that has spread to the entire world in a brief period and continues to pose a threat. The first wave corresponded with the period from February 2020 to June 2020, the Delta variant occurred around the middle of June 2021, and the Omicron wave was reported from December 2021 to February 2022. Studies have shown the association of COVID-19 infection and severity with several hematological parameters such as platelets, white blood count (WBC), lymphocytes, neutrophils (together with neutrophil-lymphocyte and platelet-lymphocyte ratio), and hemoglobin (Hgb). Objective: This study aims to compare the Delta and the Omicron variants of COVID-19 infection in a community-based hospital in New York City considering the comparison of ICU admissions in both variants. We aim to study the comparison of complete blood count (CBC) parameters and inflammatory markers of patients admitted to ICU stratified by two waves of COVID-19 infection. We aim to analyze the association of CBC parameters at admission and discharge during ICU stay in both variants. We also aim to study the association of CBC parameters at admission and discharge with ICU mortality in both variants. Methods: We conducted a retrospective observational cohort study based on data from randomly selected hospitalized patients with COVID-19 in a community-based hospital in New York City during the Delta variant and the Omicron wave. A total of 211 COVID-19-positive patients from June to July 2021 (Delta variant) and 148 patients from December to February 2022 (Omicron wave) were included in the study. A comparison was done between the basic characteristics of patients with and without ICU admissions in both variants of COVID-19. We compared the relationship of different parameters of CBC (hemoglobin (Hgb), white blood count (WBC), lymphocytes, neutrophils, and platelets) on ICU admission and further analyzed any changes associated with ICU mortality. Logistic regression was performed to evaluate the relationship of different presenting CBCs on patients’ disposition to ICU. Results: A total of 211 patients (106 female) in the Delta wave (2021 variant) and 148 patients (80 female) in the Omicron wave (2022 variant) with an average age of 60.9 ±18.10 (Delta variant) and 63.2 ± 19.10 (Omicron variant) were included in this study. In our study in an adjusted regression model (separate regression analysis for each cell count), a significant association between odds of death and WBC on admission (OR 1.12, p=0.019), WBC on discharge (OR 1.36, p<0.001), Hgb on discharge (OR 0.59, p<0.001), lymphocyte on admission (OR 0.29, p=0.018), lymphocyte on discharge (OR 0.29, p=0.007), neutrophil on admission (OR 1.18, p=0.003), and neutrophil on discharge (OR 1.32, p<0.001) were found in the Delta variant. In the adjusted regression model of the Omicron variant, a significant association between death and WBC on discharge (OR 1.21, p=0.03), Hgb on discharge (OR 0.55, p<0.001), and neutrophil on discharge (OR 1.24, p=0.002) were found. There were 45 patients (21.3%) in the Delta wave and 42 patients (28.4%) in the Omicron wave were admitted to ICU. The average length of hospital stay was seven days in the Delta wave and nine days in the Omicron wave. Conclusion: A comparative study of different clinical parameters between the Delta and the Omicron variants of COVID-19 with the correlation of ICU stay and mortality can be used as a beneficial modality in assessing the outcome of the disease. More studies need to be conducted in the future to emphasize the importance of the clinical parameters in standardizing the treatment options for COVID-19 variants.